2010
DOI: 10.1111/j.1471-0528.2009.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma orexin‐A levels in postmenopausal women: possible interaction with estrogen and correlation with cardiovascular risk status

Abstract: Objective To assess plasma orexin-A levels in a group of postmenopausal women not receiving estrogen-replacement therapy (ERT), and to compare the values with a group on ERT and a group of reproductive-age women, and to correlate the findings with some cardiovascular risk factors.Design Observational cohort study.Setting Alexandria University Hospital.Population Ninety women, in three groups: a control group of 30 healthy, reproductive-age women, 30 healthy postmenopausal women not receiving ERT, and 30 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…We provide evidence that such mechanism, by being under the negative control of leptin, may also contribute to obesity and some of its pathological consequences. Because a possible sex difference occurs in the regulation of plasma OX-A levels in humans (28,29,31) and in the POMC-driven regulation of energy expenditure and obesity in mice (30), we performed our study exclusively in male subjects. In particular, we show that OX-A acts via DAGLα-catalyzed biosynthesis of 2-AG, which then acts as an autocrine mediator on OX-1R/CB 1 R-expressing POMC neurons of the ARC to inhibit STAT3 activity and subsequently repress POMC expression and the release of the anorectic peptide, α-MSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide evidence that such mechanism, by being under the negative control of leptin, may also contribute to obesity and some of its pathological consequences. Because a possible sex difference occurs in the regulation of plasma OX-A levels in humans (28,29,31) and in the POMC-driven regulation of energy expenditure and obesity in mice (30), we performed our study exclusively in male subjects. In particular, we show that OX-A acts via DAGLα-catalyzed biosynthesis of 2-AG, which then acts as an autocrine mediator on OX-1R/CB 1 R-expressing POMC neurons of the ARC to inhibit STAT3 activity and subsequently repress POMC expression and the release of the anorectic peptide, α-MSH.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we explored whether higher levels of OX-A correlate with lower levels of α-MSH in subjects who exhibit clinical markers of obesity. Because a possible correlation between estrogen and plasma OX-A levels has been described in humans (28,29), and a sex difference occurs in the POMC-driven regulation of energy expenditure and obesity in mice (30), we tested this hypothesis exclusively in male subjects (n = 50) who had suffered from obesity for at least 5 y in comparison with n = 50 male healthy, normal-weight, volunteers. Clinical, functional, and biochemical data were obtained from each patient at the baseline, and secondary causes of obesity were excluded.…”
Section: Ox-a and α-Msh Plasma Levels Are Inversely Correlated In Severementioning
confidence: 99%
“…In humans, plasma orexin level correlates with age, with lower levels in subjects under 40, and higher levels among those aged 60 or more (Matsumura et al, 2002). In women, plasma orexin increases significantly during menopause (El-Sedeek et al, 2010). Among menopausal women, those receiving hormone replacement therapy have lower levels of plasma orexin than those receiving placebo (El-Sedeek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In women, plasma orexin increases significantly during menopause (El-Sedeek et al, 2010). Among menopausal women, those receiving hormone replacement therapy have lower levels of plasma orexin than those receiving placebo (El-Sedeek et al, 2010). Plasma orexin is known to increase after weight loss in obese children and in lean and obese adults (Bronsky et al, 2007; Heinonen et al, 2005; Komaki et al, 2001), suggesting that increase in plasma orexin is not inconsistent with orexin involvement in age-related weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptors are found on the trigeminal ganglion as well as on sensory neurons, which makes them susceptible for estrogenic modulation [55]. Further, it was demonstrated that higher orexin A blood levels are associated with a state of hypoestrogenism (menopause) [56].…”
Section: Cluster Headachementioning
confidence: 98%